2022
DOI: 10.3390/app12031746
|View full text |Cite
|
Sign up to set email alerts
|

S-Adenosylmethionine, a Promising Antitumor Agent in Oral and Laryngeal Cancer

Abstract: Squamous cell carcinoma of the head and neck (HNSCC), which includes cancers of the oral cavity and larynx, is one of the most common and highly aggressive malignancies worldwide, despite significant efforts committed in recent decades in its detection, prevention, and treatment. The intrinsic or acquired drug resistance during treatment is the main limitation to chemotherapy, increasing mortality and cancer recurrence. Therefore, there is a growing scientific interest in identifying and developing adjuvant ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 64 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…Worthy of interest in this context is to mention that AdoMet is an approved dietary supplement which can therefore be used for therapeutic purposes without the common contraindications of chemotherapy. Moreover, as documented by several clinical studies, AdoMet, at pharmacological doses, shows a low incidence of side-effects with an excellent tolerability record and no toxic or antiproliferative effects in normal, non-tumorigenic cells [ 21 ]. The ability of AdoMet to modulate miRNA expression in different cancer cell types and the well-documented potential of miRNA mimics and miRNA inhibitors to restore tumor suppressor miRNAs or to downregulate oncogenic miRNAs, respectively, greatly stimulates the design of adjuvant therapeutic approaches based on combined AdoMet/miRNAs treatments, which could allow synergistic effects resulting in increased cellular chemosensitivity and in reduced drug toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Worthy of interest in this context is to mention that AdoMet is an approved dietary supplement which can therefore be used for therapeutic purposes without the common contraindications of chemotherapy. Moreover, as documented by several clinical studies, AdoMet, at pharmacological doses, shows a low incidence of side-effects with an excellent tolerability record and no toxic or antiproliferative effects in normal, non-tumorigenic cells [ 21 ]. The ability of AdoMet to modulate miRNA expression in different cancer cell types and the well-documented potential of miRNA mimics and miRNA inhibitors to restore tumor suppressor miRNAs or to downregulate oncogenic miRNAs, respectively, greatly stimulates the design of adjuvant therapeutic approaches based on combined AdoMet/miRNAs treatments, which could allow synergistic effects resulting in increased cellular chemosensitivity and in reduced drug toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond targeting protein functions, more and more evidence has demonstrated that natural agents exert antitumor activities by altering miRNA expression, providing a new approach to develop innovative and more efficient anticancer strategies based on synergistic combinatorial therapies [ 20 ]. In this context, S-adenosyl- l -methionine (AdoMet), a multitargeted and safe FDA-approved natural compound and the universal biological methyl donor in transmethylation reactions, has emerged, over the past two decades, as a promising anticancer therapeutic agent [ 21 , 22 ]. Recently, the antiproliferative properties of AdoMet and its implication in multiple cellular processes including proliferation, differentiation, cell cycle regulation, and apoptosis in various tumor cells have been thoroughly examined in the literature [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], and several findings have highlighted the therapeutical potential of AdoMet as an effective adjuvant to chemotherapeutic agents to be used in combined therapy to overcome drug resistance [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of AdoMet as an anticancer agent has stimulated growing scientific interest taking advantage of its pleiotropic effects on different survival pathways known to be important in carcinogenesis. Recently, the antiproliferative properties of AdoMet and its involvement in multiple cellular processes including proliferation, differentiation, cell cycle regulation, and apoptosis in various cancer cells have been widely reported in the literature [16,[21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 50 years, extensive research has been conducted which suggests SAM as a potential tool for the management of various disorders. SAM is currently marketed in the United States as a dietary supplement and a viable alternative for treating depression [4][5][6], osteoarthritis [7], and liver diseases [8,9].…”
Section: Introductionmentioning
confidence: 99%